2021
DOI: 10.3390/fluids6020048
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Tribological Performance of Heterogeneous Slip/No-Slip Journal Bearing Considering Thermo-Hydrodynamic Effects

Abstract: The slip boundary has an important influence on hydrodynamic journal bearing. However, less attention has been paid to the positive effect of slip on thermal behaviour. In this study, a computational fluid dynamics (CFD) analysis investigating the thermo-hydrodynamic (THD) characteristics of heterogeneous slip/no-slip bearings running under steady, incompressible, and turbulent conditions is presented. A comprehensive analysis is made to investigate the THD behaviours of heterogeneous slip/no-slip bearings in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…The so-called heterogeneous rough/smooth pattern introduced here is inspired by the construction of heterogeneous slip/no-slip surface. As reported by numerous researchers, for example [14,[19][20][21][22][23][24], the heterogeneous slip/no-slip configuration was proven to increase the load-carrying capacity and reduce the friction force significantly. It is believed that a configuration of rough/smooth regions will lead to enhanced journal bearing properties.…”
Section: Introductionmentioning
confidence: 76%
“…The so-called heterogeneous rough/smooth pattern introduced here is inspired by the construction of heterogeneous slip/no-slip surface. As reported by numerous researchers, for example [14,[19][20][21][22][23][24], the heterogeneous slip/no-slip configuration was proven to increase the load-carrying capacity and reduce the friction force significantly. It is believed that a configuration of rough/smooth regions will lead to enhanced journal bearing properties.…”
Section: Introductionmentioning
confidence: 76%
“…This concept suggests that the slip condition appears when the fluid-solid shear stress τ surpasses a critical value τ cr . The governing factor for slip velocity is [11,44]:…”
Section: Slip Modelingmentioning
confidence: 99%
“…On the basis of the work of Zhang et al [12] and Cui et al [14], the slip/no-slip configuration carrying a rectangular shape is of special relevance in the current work. The slip is utilized partially on the convergent area to generate additional load support [11,12,14,20]. It has been demonstrated that such a pattern (i.e., a rectangular shape with a partial slip surface zone) provides superior tribological performance with higher hydrodynamic pressure in a more constrained cavitation region.…”
Section: Model Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, cavitation occurs at the divergence clearance region in full circle bearings. Finger-shaped voids that cover most of the divergence clearance region can be observed [3]. Another specific case is textured thrust bearings (such as dimple-enhanced seal-like thrust bearings), in which cavitation occurs at the tail end of each dimple [4].…”
Section: Introductionmentioning
confidence: 99%